2003
DOI: 10.1161/01.cir.0000070934.69310.1a
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Endothelial Function by Increasing High-Density Lipoprotein in Subjects With Isolated Low High-Density Lipoprotein

Abstract: Background-Loss-of-function mutations in the ATP-binding cassette (ABCA)-1 gene locus are the underlying cause for familial hypoalphalipoproteinemia, providing a human isolated low-HDL model. In these familial hypoalphalipoproteinemia subjects, we evaluated the impact of isolated low HDL on endothelial function and the vascular effects of an acute increase in HDL. Methods and Results-In 9 ABCA1 heterozygotes and 9 control subjects, vascular function was assessed by venous occlusion plethysmography. Forearm blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
159
0
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(180 citation statements)
references
References 40 publications
14
159
0
7
Order By: Relevance
“…Our study demonstrates that in offspring of diabetic parents HDL-cholesterol correlates highly with adiponectin, an association previously reported in healthy [13,14], obese [47] and type 2 diabetic subjects [48]. The link between HDL-cholesterol and EDV that we demonstrate is well established: multiple studies show low HDLcholesterol is highly predictive of endothelial dysfunction in healthy and diabetic subjects [49][50][51][52][53], and in experimental models where HDL-cholesterol is raised acutely, EDV normalises [58]. Thus, the role of HDL-cholesterol as a potential confounder in the relationship between adiponectin and endothelial function in vivo may not have been adequately considered in previous reports [25,27].…”
Section: Discussionsupporting
confidence: 81%
“…Our study demonstrates that in offspring of diabetic parents HDL-cholesterol correlates highly with adiponectin, an association previously reported in healthy [13,14], obese [47] and type 2 diabetic subjects [48]. The link between HDL-cholesterol and EDV that we demonstrate is well established: multiple studies show low HDLcholesterol is highly predictive of endothelial dysfunction in healthy and diabetic subjects [49][50][51][52][53], and in experimental models where HDL-cholesterol is raised acutely, EDV normalises [58]. Thus, the role of HDL-cholesterol as a potential confounder in the relationship between adiponectin and endothelial function in vivo may not have been adequately considered in previous reports [25,27].…”
Section: Discussionsupporting
confidence: 81%
“…The great interest for this issue, originated from previous clinical evidence that endothelial-dependent vasodilation as well as pharmacological (adenosine mediated) and metabolic coronary reserve of atherosclerotic-free or non flow-limiting atherosclerotic vessels at angiography, was reduced in hypercholesterolemic patients [12] [13] and could be normalized with the use of cholesterol-lowering strategies or NO donors [14]- [19]. Although a different contribution of total, LDL and HDL cholesterol to the impairment of coronary reserve was evidenced from previous experimental studies, they demonstrated an inhibitory effect of oxidized LDL and a protective role of HDL only on endothelium-dependent arterial vasodilation [20], concordant with clinical observations [21] [22]. On the other hand, the interplay between LDL and HDL and the association with other circulatory factors (cytokines, cell adhesion molecules) in coronary microvascular dysfunction are still partly unexplored.…”
Section: Introductionsupporting
confidence: 77%
“…The ApoAI then moves to the Golgi and binds eNOS, a process that actively recruits the necessary initiating enzymes, such as AMPK, which phosphorylates and activates the enzyme. A similar in vivo mechanism (of eNOS activation by ApoAI) is supported by human clinical studies in which it was reported that acute infusions of ApoAI phospholipid discs (reconstituted HDL) can completely normalize the decreased vasomoter response in vessels of the forearm of hypocholesterolemic men (35,36). These outcomes were a result of direct restoration of the NO pathway.…”
Section: Protein Association Between Apoai and Enosmentioning
confidence: 64%